Flexible Budget and Overhead Analysis in Pharmacy Issuers (Journal of Pharmaceutical Negative Results, 2022)
Flexible Budget and Overhead Analysis in Pharmaceutical Issuers explain and provide a theoretical description of flexible budgeting and overhead analysis in pharmaceutical companies, which aims to examine the characteristics of flexible budgets, the concept of flexible budgeting in performance evaluation, where this flexible budget relates to overhead rates that can be obtained from flexible budgets. Process and meaning The theoretical basis is used as a guide so that the research focus is in accordance with the facts in the field. The method used in this research is a case study study of literature. Case study research is research that is carried out intensively and in detail. Flexible Budget and Overhead Analysis at Pharmaceutical Issuers, it can be concluded that in preparing a flexible budget, the company can determine the level of performance of the production management section at several activity levels.